2005
DOI: 10.1523/jneurosci.4372-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Responsive Brain Region Expression Networks: Implications for Behavioral Responses to Acute Ethanol in DBA/2J versus C57BL/6J Mice

Abstract: Activation of the mesolimbic dopamine reward pathway by acute ethanol produces reinforcement and changes in gene expression that appear to be crucial to the molecular basis for adaptive behaviors and addiction. The inbred mouse strains DBA/2J and C57BL/6J exhibit contrasting acute behavioral responses to ethanol. We used oligonucleotide microarrays and bioinformatics methods to characterize patterns of gene expression in three brain regions of the mesolimbic reward pathway of these strains. Expression profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
276
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(294 citation statements)
references
References 69 publications
15
276
2
1
Order By: Relevance
“…Expression analysis was performed with samples isolated from PFC, since the PFC is activated by withdrawal (Kerns et al, 2005). Additional rationale for analysis in PFC included findings of expression differences in human alcoholics (Flatscher-Bader et al, 2006;Johansson et al, 2007;Lewohl et al, 2004), reports that PFC is a target of brain damage associated with chronic alcohol abuse (Pfefferbaum et al, 1997;Sullivan and Pfefferbaum, 2005), and that PFC can be dissected reproducibly.…”
Section: Gene Expression Differences During Etoh Withdrawalmentioning
confidence: 99%
“…Expression analysis was performed with samples isolated from PFC, since the PFC is activated by withdrawal (Kerns et al, 2005). Additional rationale for analysis in PFC included findings of expression differences in human alcoholics (Flatscher-Bader et al, 2006;Johansson et al, 2007;Lewohl et al, 2004), reports that PFC is a target of brain damage associated with chronic alcohol abuse (Pfefferbaum et al, 1997;Sullivan and Pfefferbaum, 2005), and that PFC can be dissected reproducibly.…”
Section: Gene Expression Differences During Etoh Withdrawalmentioning
confidence: 99%
“…Expression profiling with DNA microarrays has been used to identify molecular network responses to ethanol in cell culture (10,11), animal models (9)(10)(11)(12), and humans (13,14). Expression profiling has led to the identification of novel gene networks that re-…”
Section: Introductionmentioning
confidence: 99%
“…produced changes in whole brain of C57BL/6J and DBA/2J mice (high and low alcohol drinkers, respectively) in expression of genes involved in regulating cell signaling, gene regulation, and homeostasis/stress response (Treadwell and Singh, 2004). Kerns et al (2005) reported that acute i.p. ethanol injections altered, in the nucleus accumbens (ACB), prefrontal cortex and ventral tegmental area (VTA) of C57BL/6J and DBA/2J mice, expression of genes involved in glucocorticoid signaling, neurogenesis, myelination, neuropeptide signaling, and retinoic acid signaling.…”
Section: Introductionmentioning
confidence: 99%